2021
DOI: 10.1111/jan.14821
|View full text |Cite
|
Sign up to set email alerts
|

Person‐Centred Care for older people: Convergence and assessment of users’ relatives’ and staff's perspectives

Abstract: Aim Develop two psychometrically sound questionnaires to assess users’ and relatives’ opinions of Person‐Centred Care. Evaluate the convergence between the perspectives of the different agents involved in Person‐Centred Care in the older people: Users, relatives and staff. Examine the relationships between Person‐Centred Care and care quality and the users’ perceived psychological well‐being. Design We used the psychometric technology involved in the development and analysis of tests for the first objective. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…17 The aged care literature has also indicated that the longer direct care workers have been working, the better they understand their clients and the more able they are to build relationships with them. 71 The literature also suggested that high job satisfaction and lower levels of job strain enhanced the application of person-centred care strategies 72,73 Martínez et al found satisfaction among residents and their families was higher with a person-centred care approach. 73 Our review has shown that the lower the level of conflict with residents or their families, the more confident the staff feel.…”
Section: Factors Influencing Caring Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…17 The aged care literature has also indicated that the longer direct care workers have been working, the better they understand their clients and the more able they are to build relationships with them. 71 The literature also suggested that high job satisfaction and lower levels of job strain enhanced the application of person-centred care strategies 72,73 Martínez et al found satisfaction among residents and their families was higher with a person-centred care approach. 73 Our review has shown that the lower the level of conflict with residents or their families, the more confident the staff feel.…”
Section: Factors Influencing Caring Self-efficacymentioning
confidence: 99%
“…71 The literature also suggested that high job satisfaction and lower levels of job strain enhanced the application of person-centred care strategies 72,73 Martínez et al found satisfaction among residents and their families was higher with a person-centred care approach. 73 Our review has shown that the lower the level of conflict with residents or their families, the more confident the staff feel. Undoubtedly, these factors are intertwined with each other and contribute to enhancing the caring selfefficacy of direct care workers.…”
Section: Factors Influencing Caring Self-efficacymentioning
confidence: 99%
“…It is difficult to use the tools for measuring PCC in residential care facilities accurately, as only 45.5% of LTC residents’ ratings in 2019 in South Korea [ 36 ]. In addition, there was quite high convergence between the PCC evaluations from the staff, users, and relatives, with correlations ranging between 0.62 and 0.76 [ 37 , 38 ]. The impact of PCC approaches gave positive influences on stress, burnout, and job satisfaction of staff caring for people with dementia in residential care communities [ 6 ].…”
Section: Introductionmentioning
confidence: 99%